Correlative 3D cryo X-ray imaging reveals intracellular location and effect of designed antifibrotic protein–nanomaterial hybrids. Issue 45 (10th November 2021) - Groen, J.; Palanca, A.; Aires, A.; Conesa, J. J.; Maestro, D.; Rehbein, S.; Harkiolaki, M.; Villar, A. V.; Cortajarena, A. L.; Pereiro, E.
Abstract : A novel 3D cryo correlative approach locates designed therapeutic protein–nanomaterial hybrids in whole cells with high specificity and resolution. Detection of treatment-induced morphological changes, crucial for pre-clinical studies, are revealed. Abstract : Revealing the intracellular location of novel therapeutic agents is paramount for the understanding of their effect at the cell ultrastructure level. Here, we apply a novel correlative cryo 3D imaging approach to determine the intracellular fate of a designed protein–nanomaterial hybrid with antifibrotic properties that shows great promise in mitigating myocardial fibrosis. Cryo 3D structured illumination microscopy (cryo-3D-SIM) pinpoints the location and cryo soft X-ray tomography (cryo-SXT) reveals the ultrastructural environment and subcellular localization of this nanomaterial with spatial correlation accuracy down to 70 nm in whole cells. This novel high resolution 3D cryo correlative approach unambiguously locates the nanomaterial after overnight treatment within multivesicular bodies which have been associated with endosomal trafficking events by confocal microscopy. Moreover, this approach allows assessing the cellular response towards the treatment by evaluating the morphological changes induced. This is especially relevant for the future usage of nanoformulations in clinical practices. This correlative super-resolution and X-ray imaging strategy joins high specificity, by the use of fluorescence, with high spatial resolution at 30 nm (half pitch) provided by cryo-SXT in whole cells, without the need of staining or fixation, and can be of particular benefit to locate specific molecules in the native cellular environment in bio-nanomedicine.